Sexual features of depressive disorders in adolescents and young adults - Kotenko , Анастасія (Psychosomatic Medicine and General Practice, 2020)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" II Congress. It is dedicated to the sexual features of depressive disorders in adolescents and young adults.